Hyperbaric oxygen-induced acute lung injury: A mouse model study on pathogenic characteristics and recovery dynamics - Wang, Shu; Chen, Hong; Li, Zhi; Xu, Guangxu; Bao, Xiaochen (Frontiers in Physiology, 2024)
Acute lung injury (ALI) induced by hyperbaric oxygen (HBO) is notably more severe than that caused by normobaric oxygen, yet systematic research on such injury and its regression is scarce. In this study, two independent experiments were designed. In the first experiment, mice were exposed to 2 atmospheres absolute (ATA), ≥95% oxygen for 2, 4, 6, and 8 hours. Changes in lung histopathology, inflammation and expression of chemokines, alveolarcapillary barrier, and 8-OHdG were detected before and after the exposure. In the second experiment, these parameters were measured at 0 hours, 12 hours, and 24 hours following 6 hours of exposure to 2 ATA of ≥ 95% oxygen. Research indicates that ALI induced by HBO is characterized histologically by alveolar expansion, atelectasis, inflammatory cell infiltration, and hemorrhage. At 2 ATA, significant changes in the alveolar-capillary barrier were observed after more than 95% oxygen exposure for 4 hours, as evidenced by increased Evans blue (EB) extravasation (p = 0.0200). After 6 hours of HBO exposure, lung tissue pathology scores, 8-OHdG levels, and inflammatory and chemotactic factors (such as Il6, CCL2, CCL3, CXCL5, and CXCL10), intercellular adhesion molecule 1 (ICAM1), and vascular cell adhesion molecule 1 (VCAM1) were significantly elevated. Compared to lung injury caused by normobaric oxygen, the onset time of injury was significantly shortened. Additionally, it was observed that these markers continued to increase after leaving the HBO environment, peaking at 12 hours and starting to recover at 24 hours, indicating that the peak of inflammatory lung injury occurs within 12 hours post-exposure, with recovery beginning at 24 hours. This contradicts the common belief that lung injury is alleviated upon removal from a high-oxygen environment. However, EB levels, which reflect damage to the alveolar-capillary barrier, and VE-Cadherin (VE-Cad), tight junction protein 1 (ZO-1), ICAM1, and VCAM1 remained significantly altered 24 hours after leaving the HBO environment. This suggests that the alveolar-capillary barrier is the most sensitive and slowest recovering part of the lung injury induced by HBO. These findings can provide insights into the pathogenesis and progression of lung injury caused by HBO and offer references for identifying corresponding intervention targets.